A novel, effective, and feasible method for deacidifying kiwifruit wine by weakly basic ion exchange resins. (12th December 2018) - Zhong, Wu; Li, Xinyue; Yang, Hong; Li, Erhu
Abstract: In this study, an effective deacidification process for kiwifruit wine using ion exchange resins was investigated. Static adsorption experiments were conducted to screen an appropriate resin and optimize the volume ratio of resin to wine. Dynamic adsorption experiments were conducted to optimize the flow rate. Sensory and chemical analysis of the deacidified kiwifruit wine were also performed. The results demonstrated that 330 resin with a maximum adsorption capacity decreased total acid and citric acid to 4.32 and 1.39 g/L in kiwifruit wine. The acid adsorption process fitted Ho's sorption kinetic model well. The volume ratio of the 330 resin to wine and the feed flow rate were further optimized to be 1:30 and 4 mL/min. Kiwifruit wine with total acid and citric acid contents of 7.98 and 4.74 g/L was obtained, under optimum conditions, while preserving alcohol, vitamin C (Vc), flavonoids and phenol content, and improving the flavor. Practical applications: The high acidity in kiwifruit wine depress the sensory quality and attraction to consumers. Resins are applied for liquid treatment because of high efficiency, insolubility and low cost. This work showed that 330 resin treatment is a promising method to deacidify kiwifruit wine and provided an economical and effective processing method for kiwifruit processing enterprises. Monitoring acidity change and kiwifruit wine quality help enterprises better control the process. Furthermore, the easy removal of resins will greatly reduce energy consumption, resulting in lower processing cost.